Theory of Planned Behavior: Exploring the Use of Digital Mental Health Interventions in Israel. Issue 7 (29th July 2022) - Khatib, Anwar; Abo-Rass, Fareeda; Gelkopf, Marc
Abstract: Based on the theory of planned behavior (TPB), this study aimed to examine factors influencing therapist uptake of digital mental health interventions in Israel. Two hundred twenty-nine mental health professionals recruited through a convenience sample completed a background and demographic questionnaire, as well as the TPB-based electronic-therapy attitudes and process questionnaire. Regressions were used to examine the contribution of attitudes, perceived behavioral control, subjective norms, and behavioral intentions. Intention to use and use of digital interventions were significantly predicted by attitudes, subjective norms, and perceived behavioral control, as suggested by the TPB. The use of cognitive behavioral therapy (CBT) and higher perceived behavioral control increased the likelihood of using digital interventions. Having a positive attitude, having expectations/social pressure from one's professional environment, and having a sense of control over the process were found to predict the intent to use, as well as the actual use of, digital interventions.